Challenges in library collection management amid budget constraints - Ramadhan, Suci Yanti; Khoerunnisa, Lutfi; Wulandari, Yayu; Rahman, Firdaus Abdul (Faculty of Communication, Padjadjaran University, 2025)
Background: Library collection management plays a crucial role in ensuring user access to knowledge and information. However, many libraries, especially in developing countries, frequently face significant financial constraints. These limitations affect their ability to acquire, maintain, and regularly update their collections. Purpose: This study aims to analyze and identify the key challenges in library collection management amid budget constraints, highlighting core issues such as inadequate funding, acquisition prioritization, and the need for strategic resource allocation. Furthermore, this research explores innovative approaches adopted by several libraries across various regions to optimize their collections despite financial limitations, including collaboration with stakeholders, digitization efforts, and the implementation of cost-effective management strategies. Methods: This study adopts a qualitative library research method to investigate challenges and strategies in library management amid financial limitations. Data was collected through an extensive review of secondary sources. The study employs descriptive-analytical techniques to interpret qualitative data. Results: The findings indicate that libraries need to develop adaptive and flexible policies, explore ICT-based solutions, and establish partnerships to maintain the quality of collection management amid limited financial resources. This article emphasizes the importance of efficient budgeting, alternative funding sources, the application of technology, and institutional strengthening in responding to users’ needs. Thus, effective collection management under financial constraints can be realized through innovation, collaboration, strategic planning, and a sustainability-oriented vision for library collections.